A Study Of Cyanide-Glycine Synergistic Lixiviant And The Igoli Process As Suitable Replacements For Mercury Amalgamation In Artisanal And Small-Scale Gold Mining - Masuku, Wilson (Department of Chemical Engineering, 2024)
Artisanal and Small-scale Gold Mining (ASGM) operations are characterized by the use of rudimentary tools and technologies owing to limited access to capital. ASGM is predominantly a poverty-driven exercise practiced as a source of livelihood, typically in rural communities where people lack other employable skills. Globally, ASGM accounts for 20-25% of gold production, while at local scales, this number varies and can be as high as 65% in countries such as Ghana and Zimbabwe. Mercury is used in ASGM to capture gold from free-milling ores, in a process called mercury amalgamation. This is the go-to technology in most ASGM operations owing to its availability and ease of operation. However, mercury amalgamation has low recoveries in the range of 30-33% of gold from the otherwise rich gold ores typically mined in ASGM. In the amalgamation process, about 70% of the mercury used is lost to the environment with the amalgamation tailings and during the roasting process. Mercury is a toxic heavy metal, and mercury poisoning can lead to neurological and behavioural disorders and has been a major concern globally, leading to the signing of the Minamata Convention treaty. Mercury-free gold concentration and extraction methods such as shaking tables and roasting with borax have been put forward over the years, but their uptake has been very limited. The reasons for this poor uptake have never been systematically studied but it is thought that, among other reasons, it has to do with that some technologies are too complex for the ASGM context. Beyond the mercury-free technologies proposed for the ASGM sector, gold extraction and recovery in the large-scale mining sector has attracted researchers' attention for years, with a plethora of technologies having been proposed and tested. Little effort has been made to establish if any of these technologies could be a good fit for ASGM. In this study, two mercury-free technologies (cyanide-glycine lixiviant and the iGoli process) were tested to establish their effectiveness in the leaching of gold from ores sourced from two ASGM sites. The ores were characterized using QEMSCAN, XRD and XRF to identify mineral phases, and quartz was found to be the most dominant mineral. Sulphide minerals in both ores host the largest percentage of gold. The cyanideglycine lixiviant uses a combination of cyanide and glycine to improve gold extraction. The results from this showed that dissolution rate increases with an increase in glycine concentration in non-agitated systems at 3g/l NaCN while the reverse was true in agitated systems at the same cyanide concentration and when it was varied. The percentage of gold extracted in the non-agitated system after 72 hours was 36% at 5 g/l glycine, 21% at 2 g/l glycine and 19% when no glycine was added. In agitated systems at 5g/l cyanide, the highest extraction after 24 hours was 81% at 2 g/l glycine. Increasing glycine concentration led to lower gold extractions with 5 g/l and 10 g/l glycine extracting 74% and 68% respectively. This trend of decreasing extraction with an increase in glycine concentration was observed at different fixed cyanide concentrations i.e., at 1 g/l, 3 g/l and 5 g/l. The iGoli process uses hydrochloric acid and sodium hypochlorite to leach gold. The extractions were very low and reported below the detection limit of the analytical instrument, and thus they cannot be reported with confidence. However, iron was analyzed and showed a 55% extraction of the total iron in the ore. Results from these two technologies were compared to those of mercury amalgamation and benchmarked against the conventional cyanide process. Beyond the purely technical, a case study of two ASGM sites was done with the objective to observe and understand the day-to-day operations in a typical ASGM site and identify limitations and opportunities for mercury-free technology adoption. Based on insights drawn from the case studies, it was concluded that the cyanide-glycine lixiviant is relatively easy to implement given the current process operation in the ASGM sector which makes use of vat tanks that do not agitate the slurry (lixiviant + ore). However, the observed poor recoveries associated with the technology in non-agitated systems would be a limitation. When more profits are realized, the ASGM practitioners can upgrade to agitated systems and add hydrogen peroxide as an oxidizing agent to improve extraction.